(untitled) (Hekima Review, 2013)
Reinhard Neudecker, SJ, who has been professor of rabbinic literature at the Pontifical Biblical Institute in Rome since 1978 offers here an insightful, stimulating and informative study of Matthew’s so-called antitheses (Matt 5:21-48) in the light of early rabbinic literature. Trained in theology (1971 Dr. theol. Innsbruck, Austria) and rabbinic literature (PhD 1978 at Hebrew Union College in Cincinnati, USA), the author brings together his competence and experience in order to provide adequate and fuller background information for the reader not well acquainted with Jewish sources. In his own words, his study aims “to go back, as far as this is possible, to the situation in the life of Jesus and his contemporary Scribes and Pharisees”.